UPAYA PENINGKATAN PENDAPATAN MELALUI PELATIHAN PEMBUATAN CAKE DAN PENJUALAN BERBASIS WEB - Hery Haerudin (BERNAS: Jurnal Pengabdian Kepada Masyarakat, 2021)
The corona virus pandemic that hit our country in the last 1 year has had an impact not only on the health sector but also on the economic sector, almost all levels of society feel the consequences. The existence of restrictions on activities outside the home has caused a decrease in business activities, even many of them business people who went bankrupt, resulting in an increase in the unemployment rate and loss of income for the community, including the community in RW 26 Cinunuk Village, Cileunyi District. With the problems mentioned above, this PKM activity is carried out with the aim of helping the community, especially those in RW 26 in increasing their family income by providing cake making training and training on selling via the web online for PKK mothers who are in RW 26 Village. Cinunuk, Cileunyi District, Bandung Regency. With the training and assistance provided in this PKM activity, it is hoped that the community, especially PKK RW 26 women as partners, have skills and can develop their creativity in making cakes, as well as proficient in selling through online websites, so that during a pandemic like now This can still provide income for his family.